Monitoring plasmonic hot-carrier chemical reactions at the single particle level. (27th February 2019) - Simoncelli, Sabrina; Pensa, Evangelina L.; Brick, Thomas; Gargiulo, Julian; Lauri, Alberto; Cambiasso, Javier; Li, Yi; Maier, Stefan A.; Cortés, Emiliano
Abstract : Nanoscopic inspection of reactivity in single plasmonic photocatalysts. Abstract : Plasmon excitation in metal nanoparticles triggers the generation of highly energetic charge carriers that, when properly manipulated and exploited, can mediate chemical reactions. Single-particle techniques are key to unearthing the underlying mechanisms of hot-carrier generation, transport and injection, as well as to disentangling the role of the temperature increase and the enhanced near-field at the nanoparticle–molecule interface. Gaining nanoscopic insight into these processes and their interplay could aid in the rational design of plasmonic photocatalysts. Here, we present three different approaches to monitor hot-carrier reactivity at the single-particle level. We use a combination of dark-field microscopy and photoelectrochemistry to track a hot-hole driven reaction on a single Au nanoparticle. We image hot-electron reactivity with sub-particle spatial resolution using nanoscopy techniques. Finally, we push the limits by looking for a hot-electron induced chemical reaction that generates a fluorescent product, which should enable imaging plasmonic photocatalysis at the single-particle and single-molecule levels.